Guiding the Congregation through Collaborative Study of Traditional Islamic Texts on Fiqh to Enhance Understanding of Acts of Worship at Baitul Muttaqin Mosque, Banyuwangi - Ilham Nur Kholiq; Yayah Robiatul Adawiyah; Sofi Faiqotul Hikmah (CENDEKIA: Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to improve the worship understanding of congregants through the Sinau Bareng (collaborative learning) of classical Islamic jurisprudence (kitab kuning fiqh) at Baitul Muttaqin Mosque, Banyuwangi. The program was conducted using the Participatory Action Research (PAR) approach, which actively involved mosque congregants, mosque administrators, and facilitators in identifying problems, planning activities, implementing learning sessions, and evaluating outcomes. The activities included regular fiqh studies, interactive discussions, worship consultations, and practical guidance on daily religious practices. The results demonstrated an increase in congregants’ understanding of Islamic jurisprudence related to worship, greater participation in mosque-based educational activities, and the development of a collaborative learning culture within the community. Furthermore, the program strengthened the role of the mosque as a center for religious education and community empowerment. Social changes were reflected in the congregants’ improved awareness of performing worship based on sound religious knowledge and their increased engagement in collective religious learning. In conclusion, the Sinau Bareng model of studying classical fiqh texts proved effective in enhancing religious literacy, worship practices, and community participation while fostering sustainable religious empowerment within the mosque community